High-Impact Practices: Evaluating Impact on Adult Learners’ Retention - Alsarhan, Alaa (Experiential Learning and Teaching in Higher Education, 2024)
High-impact practices (HIPs) are expected to engage traditional and nontraditional student populations at different levels and types. As a result, student retention is expected to increase. At Utah Valley University (UVU), we developed a visualization dashboard to measure the impact of individual and collective HIPs on students' persistence and retention using propensity score matching (PSM). This study's findings describe HIPs' effectiveness as a tool for supporting Adult Learners students' retention and persistence. Compared to peers who did not participate in HIPs, Adult Learners students involved in HIPs were retained at higher rates.